2020
DOI: 10.1007/s40279-020-01308-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the Acute: Chronic Workload Ratio (ACWR) Associated with Risk of Time-Loss Injury in Professional Team Sports? A Systematic Review of Methodology, Variables and Injury Risk in Practical Situations

Abstract: Is the acute:chronic workload ratio (ACWR) associated with risk of timeloss injury in professional team sports? A systematic review of methodology, variables and injury risk in practical situations ABSTRACT Background The acute:chronic workload ratio (ACWR) is an index of the acute workload relative to the cumulative chronic workloads. The monitoring of physical workloads using the ACWR has emerged and been hypothesized as a useful tool for coaches and athletes to optimize performance while aiming to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 88 publications
0
53
0
3
Order By: Relevance
“…The training load dataset file was imported into Matlab (Matlab 2018b, MathWorks) to programmatically produce the data combinations required for analysis. For each daily load value per player, each possible ACWR calculation method was produced, including RA and EWMA [14], coupled and uncoupled [7,36] and each time frame (3,5,7,9,14,21,28,35). This procedure resulted in the following ACWR measure for each player each day (▶ Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…The training load dataset file was imported into Matlab (Matlab 2018b, MathWorks) to programmatically produce the data combinations required for analysis. For each daily load value per player, each possible ACWR calculation method was produced, including RA and EWMA [14], coupled and uncoupled [7,36] and each time frame (3,5,7,9,14,21,28,35). This procedure resulted in the following ACWR measure for each player each day (▶ Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…In team sports, it is more complicated because of the influence of contextual factors (Brito et al, 2016;Oliva-Lozano et al, 2020) affecting both internal and external load parameters in a different manner (Fox et al, 2020). The picture is even more complex if we consider that the current ACWR literature has found different relationships between ACWR indices generated with different internal [e.g., session rating of perceived exertion (sRPE)] and external (e.g., accelerations) load parameters in team sports characterized by different psycho-physiological demands (Andrade et al, 2020;Griffin et al, 2020). This means that the relationships found between ACWR and injury risk are not interchangeable among team sports, therefore suggesting the greater weight of extrinsic factors within this relationship, as it has been also suggested that the strength of the relationships between internal and external load parameters in team sports depends upon the training mode (McLaren et al, 2018).…”
Section: Differences In Physiological Demands Between Individual and mentioning
confidence: 99%
“…The ACWR is currently in the spot light of sport sciences (Griffin et al, 2020;Maupin et al, 2020). While some emerging evidence suggests that it is a valid method to identify an increased injury risk (Andrade et al, 2020), other authors have pointed out its methodological limitations and even questioned its validity (Impellizzeri et al, 2020;Wang et al, 2020). Proponents of the ACWR approach argue that athletes are at greater risk of sustaining a time-loss injury when the ACWR is higher relative to a lower or moderate ACWR (Andrade et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While early introductory research concentrated on the relationship between load parameters and injury, this may have led to the belief that these were the only measures of importance, however it has since been stated that these measures should only be a component of a wide variety of measures [9][10][11]. We agree that no single metric can clearly state the risk of injury or state of preparedness of an athlete and therefore review why load monitoring is far more than any individual metric, and how it can play a vital role in informing performance-related decisions.…”
mentioning
confidence: 99%